Method of Memorizing Al-Qur'an According to Baduwailan - Zainal Arifin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
The purpose of this study is to explore the urgency of memorizing al-Qur'an education and how the theory of memorizing al-Qur'an according to Baduwailan. This research is a qualitative research with a type of library research, and data analysis techniques using inductive and deductive. The findings of this study can be concluded: first, memorizing the Qur'an is very important as a scientific foundation in the field of religion and other sciences. Earlier scholars required memorization of the Qur'an as the beginning of learning before learning other sciences. Memorizing the Qur'an is a tradition of Salaf Salih which continues to be passed on until this time until the age to come. Therefore, the spirit of memorization must continue to be encouraged in the midst of Muslims. Second, the theory of memorizing the Qur'an according to Baduwailan is as follows: (a) Ikhlash; (b) Correcting pronunciations and readings before memorizing; (c) Determine daily memorization; (d) Establish memorization before continuing; (e) Using a Manuscripts for Tahfizh; (f) Memorizing While Understanding Verses; (g) Binding Between the Beginning and End of the Letter; (h) Keep memorizing deliberately and learn. Keywords: Memorization, al-Qur'an, Baduwailan